Brown adipose tissue harbors a distinct sub-population of regulatory T cells - Medrikova, Dasa; Sticht, Carsten; Gretz, Norbert; Schafmeier, Tobias; Herzig, Stephan (PLOS ONE, 2015)
Regulatory T (Treg) cells are critical determinants of both immune responses and metabolic control. Here we show that systemic ablation of Treg cells compromised the adaptation of whole-body energy expenditure to cold exposure, correlating with impairment in thermogenic marker gene expression and massive invasion of pro-inflammatory macrophages in brown adipose tissue (BAT). Indeed, BAT harbored a unique sub-set of Treg cells characterized by a unique gene signature. As these Treg cells respond to BAT activation upon cold exposure, this study defines a BAT-specific Treg sub-set with direct implications for the regulation of energy homeostasis in response to environmental stress.